2013
DOI: 10.1007/s10238-013-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

CA19-9 and CA242 as tumor markers for the diagnosis of pancreatic cancer: a meta-analysis

Abstract: Pancreatic cancer has the worst prognosis of any gastrointestinal cancer, with the mortality approaching the incidence. Early detection is crucial for improving patient prognosis. We therefore performed a meta-analysis to evaluate and compare the sensitivity and specificity of CA19-9 and CA242 in pancreatic cancer. We searched PubMed, EMBASE, and the Cochrane Library for studies that evaluated the diagnostic validity of CA19-9 and CA242 between January 1966 and March 2011. Meta-analysis methods were used to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 24 publications
2
43
1
Order By: Relevance
“…Due to its occult nature, diagnostic difficulties, rapid development, and high mortality, it is often beyond surgical removal when the patients are diagnosed [1,2]. Cryoablation by Cryocare system has been widely used in breast cancer, liver cancer, kidney cancer, etc., which provides a new therapeutic tool for benign and malignant tumors that cannot be surgically removed [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its occult nature, diagnostic difficulties, rapid development, and high mortality, it is often beyond surgical removal when the patients are diagnosed [1,2]. Cryoablation by Cryocare system has been widely used in breast cancer, liver cancer, kidney cancer, etc., which provides a new therapeutic tool for benign and malignant tumors that cannot be surgically removed [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Several other biomarkers such as carcinoembryonic antigen (CEA) and carbohydrate antigen 242 (CA242) were identified as biomarkers for the diagnosis, prognosis and surveillance of PC. However, these markers are non-specific for PC and also lack sensitivity or specificity [5, 6]. Therefore, the identification of new and reliable noninvasive biomarkers is required for more accurate patient stratification and clinical care in PC patients.…”
Section: Introductionmentioning
confidence: 99%
“…We found that CA242 levels were elevated in a variety of digestive system cancers, including pancreatic cancer, gallbladder cancer, cholangiocarcinoma, colorectal cancer, and gastric cancer, which was consistent with previous reports. The AUC values of the ROC curves for pancreatic cancer, gallbladder carcinoma, and cholangiocarcinoma were all greater than 0.8, but only pancreatic cancer has been studied in detail [4,10,13,17,22,[25][26][27]. Previous studies have shown that CA242 alone or in combination with other biomarkers can predict the diagnosis, progression, and prognosis of pancreatic cancer [4, 7, 10, 12-16, 23, 24].…”
Section: Discussionmentioning
confidence: 99%